2022
DOI: 10.1111/1758-5899.13072
|View full text |Cite
|
Sign up to set email alerts
|

The Donkey Skin Trade: Challenges and Opportunities for Policy Change

Abstract: The use of animal derivatives in traditional Chinese medicine (TCM) dates back more than 5000 years. Donkey skins are one such animal derivative, the skins are used to produce ejiao, which is a luxury product and believed by some to have a variety of health benefits. The increasing demand for ejiao is putting the global donkey population at risk. In China between 1990 and 2018 the donkey population decreased by 77 per cent, as a consequence donkeys are largely being sourced from Africa to meet the demand. In l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…While previous research has explored the impact of Chinese import competition on economic variables such as manufacturing employment (Autor et al, 2013;Pierce & Schott, 2016) and workers' earnings (Autor et al, 2014;Dix-Carneiro et al, 2023), there is a smaller body of work focusing on the demand-side effects of China's ascendancy, especially in those natural-resource based markets. Previous research has shown that ejiao market and donkey hide trade has led to detrimental effects on rural communities livelihoods in African countries, where donkeys are important assets (Carder et al, 2019;Goodrum et al, 2022;Maggs et al, 2023). Our results point out, however, to a resource-boom effect: international demand makes these previously worthless animals valuable.…”
Section: Introductioncontrasting
confidence: 43%
See 2 more Smart Citations
“…While previous research has explored the impact of Chinese import competition on economic variables such as manufacturing employment (Autor et al, 2013;Pierce & Schott, 2016) and workers' earnings (Autor et al, 2014;Dix-Carneiro et al, 2023), there is a smaller body of work focusing on the demand-side effects of China's ascendancy, especially in those natural-resource based markets. Previous research has shown that ejiao market and donkey hide trade has led to detrimental effects on rural communities livelihoods in African countries, where donkeys are important assets (Carder et al, 2019;Goodrum et al, 2022;Maggs et al, 2023). Our results point out, however, to a resource-boom effect: international demand makes these previously worthless animals valuable.…”
Section: Introductioncontrasting
confidence: 43%
“…Donkeys are slaughtered in these regions, and their skins are exported to Chinese factories for ejiao production. This globalized trade has exerted immense pressure on donkey populations worldwide, leading to concerns over animal welfare, livelihoods dependent on donkeys, and the sustainability of donkey populations (Bennett & Pfuderer, 2020;Gameiro et al, 2021;Goodrum et al, 2022;Waters, 2019).…”
Section: Ejiao and Donkeys' Hide Tradementioning
confidence: 99%
See 1 more Smart Citation
“…One novel, and of considerable concern to some, is the inter-continental value chain for “ejiao”, a gelatine produced from donkey skin and used in traditional Chinese medicine and beauty products. Africa is the epicentre of this trade, which has depleted stocks and resulted in an illegal trade of donkeys (Goodrum et al 2022 ). Replacing stocks through breeding is slow, as donkeys have low fertility and long gaps between offspring (Brooke 2020a ).…”
Section: Methodsmentioning
confidence: 99%
“…In the context of modern agriculture and the evolving role of donkeys in agricultural production, this discourse delves into the increasing utilization of donkey products, with particular emphasis on the medicinal value attributed to ejiao, derived from donkey hide (Maigari et al, 2020;Goodrum et al, 2022;Yan et al, 2023). It is of particular note that the dermal layer of donkey hide, enriched with collagen, assumes a pivotal role in the preparation of ejiao.…”
Section: Introductionmentioning
confidence: 99%